On Generalized Carleson Operator with Application in Walsh Type Wavelet Packet Expansions: Shyam Lal, Susheel Kumar - Team, Support (Thai Journal of Mathematics, 2021)
In this paper, two new theorems on generalized Carleson operatorfor a Walsh type wavelet packet system and for periodic Walsh typewavelet packet expansion of a function f L^p [ 0,1 ), 1 < p < ∞, have been established.